Kinetic and Isotherm Analysis of TiO₂/UiO-66-NH₂ Composites for Treating Produced Water Contaminants - Kusworo, Tutuk Djoko; Budiyono, Budiyono (Waste Technology, 2024)
The TiO₂/UiO-66-NH₂ composites synthesized through a hydrothermal method, demonstrated a significant enhancement in photocatalytic activity under visible light, offering a promising solution for the treatment of pollutants in produced water. These composites exhibited exceptional photocatalytic adsorption and degradation capabilities, efficiently removing various contaminants. The adsorption process during pollutant removal was effectively modeled by both the Freundlich and Langmuir isotherms, indicating the heterogeneous nature of the adsorption sites and the monolayer adsorption behavior, respectively. The composites achieved impressive removal efficiencies of 88.46% for NH₃-N and 81.97% for total dissolved solids (TDS), underscoring their potential to address common pollutants in produced water. UV-vis spectroscopy analysis revealed a band gap energy of 2.28 eV for the TiO₂/UiO-66-NH₂ composites, which is lower than that of pure TiO₂, contributing to enhanced photocatalytic performance under visible light. This reduced band gap improves the material's ability to absorb visible light, thereby facilitating more efficient degradation of organic pollutants. Furthermore, the pseudo-second-order kinetic model best described the adsorption process for both TiO₂ and TiO₂@UiO-66-NH₂ composites, suggesting that chemisorption is the dominant mechanism for NH₃-N removal. This indicates that the composites exhibit a high affinity for NH₃-N, effectively removing it from produced water. Overall, the TiO₂/UiO-66-NH₂ composites provide a promising approach for mitigating contaminants in produced water, demonstrating their potential for use in both environmental and industrial water treatment applications.